Palmer Midcarpal Instability: An Algorithm of Diagnosis and Surgical Management - Ho, Pak-Cheong; Tse, Wing-Lim; Wong, Clara Wing-Yee (Journal of Wrist Surgery, 2017)
Background Palmar midcarpal instability (PMCI) is an uncommon form of nondissociative carpal instability. However, it is an important cause of chronic ulnar wrist pain. Diagnosis can be difficult and high index of suspicion is mandatory. Pathomechanics and optimal treatment of PMCI remain uncertain. We propose an algorithm of clinical diagnosis and evaluate the outcome of our management.Materials and Methods Between 2000 and 2011, 16 patients, including 7 males and 9 females, of a mean age of 33.9 diagnosed with PMCI were reviewed for their clinical, radiologic, and arthroscopic features. All patients presented with ulnar wrist pain in their dominant hands except in one. Initial management included a disease-specific anticarpal supination splint. Refractory cases were evaluated by arthroscopy and treated by arthroscopic thermal shrinkage using radiofrequency appliance as an interim or definite surgical intervention. Shrinkage was targeted at the ulnocarpal ligament at the radiocarpal joint and triquetrohamate ligament at the midcarpal joint. Nonresponsive or recurrent cases were managed by a novel technique of dorsal radiocarpal ligament reconstruction procedure using a pisiform-based split flexor carpi ulnaris (FCU) tendon graft.Results In all cases, the midcarpal clunk test was positive with pain. Other common clinical features included lax ulnar column, carpal supination, volar sagging of the wrist, increased pisostyloid distance, wrist pain aggravated by passive hand supination and not by passive forearm supination, and increased wrist pain upon resisted pronation, which could be partially alleviated by manually supporting the pisostyloid interval. Common arthroscopic findings were excessive joint space at triquetrohamate interval and reactive synovitis over the ulnar compartments. Nine patients (56.3%) responded well to splinting alone at an average follow-up of 3.3 years. Arthroscopic thermal shrinkage was performed in five patients with recurrence in two patients. Five patients received split FCU tendon graft for ligament reconstruction. All patients showed improvement in the wrist performance score (preop 21.0, postop 36.6 out of 40) and pain score (preop 10.0, postop 2.2 out of 20) at the final follow-up of average 86 months (range: 19–155 months). Grip strength improved from 66.9 to 82.0% of the contralateral side. Wrist motion slightly decreased from a flexion/extension arc of 132 to 125 degrees. Three patients were totally pain free, one had mild pain, and one had moderate fluctuating pain. All patients returned to their original works. X-ray showed no arthrosis.Conclusion PMCI is an uncommon but significant cause of chronic ulnar wrist pain. We have developed a clinical algorithm for diagnosis of the condition. The natural history seems to favor a benign course. Conservative treatment with an anticarpal supination splint is recommended as the initial management. Surgical options for resistant cases include arthroscopic thermal shrinkage or soft tissue reconstruction. The reconstruction of the dorsal radiocarpal ligament using a pisiform-based split FCU tendon graft provides reliable restoration of the carpal stability with good long-term outcome and few complications. This should be considered a viable alternative to limited carpal fusion.
Keywords: carpal instability; ligament reconstruction; thermal shrinkage; wrist; surgery; palmar midcarpal instability